The Highs and Lows of P Supply in Medical Cannabis: Effects on Cannabinoids, the Ionome, and Morpho-Physiology - Shiponi, Sivan; Bernstein, Nirit (Frontiers in Plant Science, 2021)
Environmental conditions, including availability of mineral nutrients, affect secondary metabolism in plants. Therefore, growing conditions has significant pharmaceutical and economic importance for Cannabis sativa. Phosphorous is an essential macronutrient that affects central biosynthesis pathways. In this study, we evaluated the hypothesis that P uptake, distribution and availability in the plant affect the biosynthesis of cannabinoids. Two genotypes of medical 'drug-type' cannabis plants were grown under five P concentrations of 5, 15, 30, 60 and 90 mgL-1 (ppm) in controlled environmental conditions. The results reveal several dose-dependent effects of P nutrition for both genotypes on the cannabinoid profile, as well as on the ionome and plant functional-physiology, thus supporting the hypothesis. i. P concentrations ≤ 15 mgL-1 were insufficient to support optimal plant function, and reduced photosynthesis, transpiration, stomatal conductance and growth. ii. 30-90 mgL-1 P were within the optimal range for plant development and function, and 30 mgL-1 P was sufficient for producing 80% of the maximum yield. iii. Ionome: About 80% of the plant P accumulated in the unfertilized inflorescences. iv. Cannabinoids: P supply higher than 5 mgL-1 reduced THCA and CBDA concentrations in the inflorescences up to 25%. Cannabinoid concentrations decreased linearly with increasing yield, consistent with a yield dilution effect, but the total cannabinoid content per plant increased with increasing P supply. These results reveal contrasting trends for effects of P supply on cannabinoid concentrations, which were highest under < 30 mgL-1 P, vs. inflorescence biomass that was highest under of 30-90 mgL-1 P. Thus, P regime should be adjusted to reflect production goals. The results demonstrate the potential of mineral nutrition to regulate cannabinoid metabolism and optimize pharmacological quality.